Eruptive Syringoma—Clinical, Dermoscopic, and Reflectance Confocal Microscopy Features - Agnieszka Rydz; Jakub Żółkiewicz; Michał Kunc; Martyna Sławińska; Michał Sobjanek; Roman J. Nowicki; Magdalena Lange (Diagnostics)
We present an interesting image of eruptive syringoma confirmed by histopathological assessment in a 37-year-old male who was consulted due to numerous brownish small macules and papules resembling maculopapular cutaneous mastocytosis (MPCM). We show difficulties in diagnosing ES, given its rare occurrence and resemblance to other dermatological disorders. Moreover, we discuss the role of dermoscopy and reflectance confocal microscopy in the differential diagnosis of syringoma.